News Literacy and Public Service News Broadcasting: Is There a Connection? Evaluating News Literacy Among Viewers and Non-Viewers of PSB News Programming in Austria - Kimberly Callecod-Weinrich; Janez Krek (SAGE Open)
News literate individuals have the requisite knowledge, skills, and motivation to navigate today’s complex news ecosystems and participate in civic life. This study’s objective was to use survey research to evaluate news literacy and its attitudinal dimensions among viewers and non-viewers of television news programming on public service broadcasters (PSBs), drawing on an existing measurement model developed by Maksl, Ashley, and Craft. Results obtained from a representative sample of adult news consumers in Austria ( n  = 492) suggest that regular PSB news viewers are significantly more likely to exhibit the characteristics of more highly news literate individuals, even when controlling for age and educational level. Establishing a baseline measurement of news literacy in this cohort in the midst of a transforming media landscape fills a research gap in the nascent discipline and provides a useful point of reference for future scholarship.